The Level of Anxiety among Jordanian Family Members during COVID Second Wave - Salameh, Maram Jaser Salem Bani; Nazzal, Kamal (International Journal of Membrane Science and Technology, 2023)
This study examines the complex emotional and physiological landscape of fear felt by Jordanian households during the second wave of the COVID-19 epidemic. The research looks at how gender, age, occupation, and marriage status affect stress levels in these households. Using a quantitative methodology, data were gathered through a structured survey sent to 300 households in Amman. These findings highlight the role that individual demographics play in determining the extent to which one suffers from anxiety. Anxiety was more prevalent in women than in men, and it increased with age in both sexes. Individuals in certain occupations and those who had been married for extended periods of time also reported higher anxiety levels. The results illuminate the need of individualized therapies catering to various family settings by highlighting the relationship between demographic variables and anxiety reactions. The study's thorough framework is helpful for comprehending the complex nature of anxiety in Jordanian homes. These findings may be used to design more effective support programs, such as those geared toward women or older adults, or those used in the workplace or the home. These kinds of programs may help Jordanian families thrive by responding to the specific threats presented by the epidemic. Policymakers, healthcare providers, and mental health specialists may lessen the toll the epidemic has on family members' emotional and physical health if they recognize the unique roles that demographics play in people's fear.